Revolutionizing Healthcare: The Role of Artificial Intelligence in Cancer Medicine and Resistance Management - George Edison (Information Technology and Science (ITScience), 2024)
I will write about use of AI in healthcare and how it is altering practice of medicine and advancement in the practice of research in general healthcare. This paper shall therefore make efforts at highlighting the critical use of AI in dealing with antibiotic stewardship and resistance, synthesize new ideas involving the concept to enhance the utilization of antibiotics, reduce on resistance as well as promote the wellbeing of patients. Such comparability is made to improvement in cancer treating, where the AI is enhancing the early diagnoses, unique patient treatment, and biopharmaceuticals and cancer resistances tracking. However, with the use of machine learning, predictive modelling and data analytics, AI is providing solution based on problems that cannot be solved directly using the diseases and cancer. Thus, despite the fact that this paper provided just some examples of AI’s application in two fairly significant spheres of healthcare, it is possible to confidently state that employing the given technologies may bring efficient amendment in the spheres of medical practice and enhance the health of people all over the globe.